A NEW CSA HEARING PROTECTION STANDARD - Behar, Alberto (Canadian Acoustics, 2014)
The first CSA hearing protectors’ standard was published back in 1965. Since then, there have been 6 editions, the last issued in 2002. There is a need to update the standard because manufactures improve their products and introduce new types, also because of advances in methods for testing protectors and in analysis oft the results. The big problem has been (and is still) how to equate the lab testing results with real life situations. The present edition of the standard appears under the name of Z94.2-14 Hearing Protection Devices – Performance, selection, care and use. It has just gone through a mandatory Public Review and is being prepared for publication, probably before the year end. This edition expands on performance requirements and rating schemes to help the user to select the device most appropriate for a given work situation. It now includes the widely used Noise Reduction Rating (NRR) and a derating scheme to obtain more reliable noise level estimates. Potential use of Field Attenuation Estimation Systems (FAES) is also included. This Standard should be used in conjunction with CSA Z1007, Management of occupational hearing conservationprograms, that deals with all aspects of the creation and management of hearing conservation programs.